Simultaneous synthesis and incorporation of zinc oxide particles in bamboo pulp through chemical and biological methods for antimicrobial paper - Sobri, Zakiah (2019)
Metal oxide nanoparticles such as zinc oxide have been recognized for its potential use in health-related and packaging application. This inorganic compound can be applied for antimicrobial paper. The objectives of this study were to synthesized and incorporate zinc oxide particles simultaneously in bamboo pulp and subsequently used for antimicrobial paper. The effect of pulp type and synthesis methods on the formation of zinc oxide-pulp are evaluated and characterized by Field Emission Scanning Electron Microscope and Scanning Electron Microscope with Energy Dispersive X-Ray Analysis (FESEM-EDX/SEM-EDX), Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD). The morphology of chemical synthesized zinc oxide-pulp appeared in the range of 64.1 nm to 87.5 nm while biosynthesized zinc oxide-pulp size range from 0.33 μm to 2.00 μm with spherical, rod and hexagonal shapes. Biosynthesized zinc oxide-pulp showed higher intensity and a broader band of FTIR spectrum at 400 cm-1 to 600 cm-1 indicated less impurity content compare to chemical synthesized zinc oxide-pulp. Narrow and sharp peaks at 20° of 2O of XRD suggested that more crystalline zinc oxide-pulp is formed by biological method. The antimicrobial property of zinc oxide-pulp has demonstrated stronger antimicrobial activities against Staphylococcus aureus (ATCC 43300), Salmonella choleraesuis (ATCC 10708) and Escherichia coli (ATCC 25922) on biosynthesized zinc oxide-pulp samples compared to chemical synthesized zinc oxide-pulp. Unbleached zinc oxide-pulp has stronger antimicrobial activity than bleached zinc oxide-pulp and significant relationships among the parameters on antimicrobial properties are presented by ANOVA analysis suggested that optimum temperature for biosynthesis zinc oxide-pulp is 70℃ with 0.5 M and 0.7 M of zinc chloride with 100 ml of algae extract. Reduction of mechanical property of zinc oxide-paper developed via chemical method is because of the interruption made by zinc oxide particles at bonded area of fibre.